ナンキョク バンダコ ノ ビリョウ キンゾク ノ ブンプ ト ソノ キゲン - 増田, 宣泰; マスダ, ノリヤス; 西村, 雅吉; ニシムラ, マサキチ; 鳥居, 鉄也; トリイ, テツヤ; Masuda, Noriyasu; Nishimura, Masakichi; Torii, Tetsuya (1982)
P(論文) 1978-79年のフィールドシーズンに南極バンダ湖(水深68m)で表層から底層まで10層の採水を行い, その微量金属(Al, Fe, Ni, Cu)を定量した。銅は塩素と同様な分布を示した。アルミニウムは水深によらずほぼ一定の値を示した。鉄は55m以浅ではほぼ一定の値を示すが, それ以深で急激な濃度増加が認められた。これは3価の鉄が底付近で還元され上方に拡散し, この過程をくり返したためと考えられる。湖水中で大きな除去過程がない(対塩素比が水深によらずほぼ一定)と考えられる銅を微量金属の代表として, その起源を考察した。湖水のCu/Na比は海水に比べ3桁以上高い値であり, またCu/Na比は南極点などの雪氷の値に近似しており, エーロゾル-降雪-氷河-氷河融水-バンダ湖の径路が微量金属の起源と考えられる。 In 1978-79 field season, water samples were collected vertically at Lake Vanda. The concentrations of Al, Fe, Ni, and Cu were determined. The vertical profile of copper is similar to that of chlorinity. Aluminium has constant value from the surface to the bottom. The concentrations of iron are also constant from the surface to 55m but below this layer iron increases abruptly. In the layer above 55m, iron should be present as trivalent solid form and precipitated to the bottom where iron is reduced and diffused upward. This process could be repeated to account for the iron distribution of the observed profile. Copper shows a good correlation with chlorinity which is not removed significantly in the lake. The copper to sodium ratio of sea water is three orders of magnitude smaller than that of deep water of the lake, which has a similar ratio to Antarctic snow. The data supports that the origin of copper is air-borne particles via glacier and glacial melt water. departmental bulletin paper